Local Wisdom-Based Policy Innovation in Indonesia During 2018-2021 - Suranto, Suranto; Darumurti, Awang (Journal of Governance and Public Policy, 2024)
Several studies on the innovation of Indonesian public services only provide general and less specific descriptions of inclusive public services based on local wisdom. This study aims to find innovative models of local wisdom-based public services in Indonesia. This study is a descriptive-exploratory study, and the research method is an archival one emphasizing secondary data use. The findings revealed that  (1) Local government dominated policy innovation proposals based on local wisdom compared to the central government because of the proximity aspect of service distance to objects, so the type of service is specific. 2) Product-oriented service types dominated service innovation due to specific, urgent, and critical service needs that must be resolved immediately. 3) Innovation with the outcome of problem-solving was very dominant because it is related to critical service issues that require solving problems by minimizing existing local cultural clashes. 4) The sectors of education, community empowerment, food security, environmental preservation, and the health sector almost evenly influenced service policy innovations based on local wisdom, because it is a wedge between direct contact with basic community services and the culture adopted by local communities. 5) Innovator originating from Java and Outside Java had competed quite dynamically over the last four years, because Outside Java excelled in the quantity of both organizations and local communities, while Java excelled in its human resources and infrastructure's quality.